2012
DOI: 10.2135/cropsci2011.08.0406
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for Seed Tocopherol Content in Sunflower

Abstract: Tocopherols are natural antioxidants with vitamin E activity. Sunflower seeds contain predominantly α‐tocopherol (>950 g kg−1 tocopherols), which is the tocopherol form exhibiting the highest vitamin E activity. The objective of this research was to study the genetic basis of total seed tocopherol content in sunflower (Helianthus annuus L.). Quantitative trait loci (QTL) analysis was conducted in two mapping populations derived from crosses between lines with increased (IAST‐413) and reduced (IAST‐522) tocophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In this study we are measuring a-tocopherol, the most biologically active form of vitamin E. The U.S. Department of Agriculture (USDA), Agricultural Research Service reports vitamin E content for a Florida-grown 'Hass' avocado to be %19.7 mgÁg -1 . A study of tocopherol content in sunflower (Helianthus annuus) seeds reported a heritability ranging from 0.67 to 0.78 (Del Moral et al, 2012), making vitamin E a good candidate for selection in that species.…”
mentioning
confidence: 99%
“…In this study we are measuring a-tocopherol, the most biologically active form of vitamin E. The U.S. Department of Agriculture (USDA), Agricultural Research Service reports vitamin E content for a Florida-grown 'Hass' avocado to be %19.7 mgÁg -1 . A study of tocopherol content in sunflower (Helianthus annuus) seeds reported a heritability ranging from 0.67 to 0.78 (Del Moral et al, 2012), making vitamin E a good candidate for selection in that species.…”
mentioning
confidence: 99%
“…It was shown in sunflower that a genetic variability for their content could be exploited in breeding and QTL were mapped (Del Moral et al, 2012, Haddadi et al, 2011, Merah et al, 2012. The tocopherols B. napus orthologs of Arabidopsis genes were identified and functionally analyzed (Fritsche et al, 2014), providing precise tools for tocopherol profile modifications by breeding.…”
Section: Quality Traits: Diversification a Step Aheadmentioning
confidence: 99%
“…Therefore, given the fact that tocopherol content is a multifactorial complex polygenic trait, several studies mapped QTL that control the seed contents of α-Toc, β-Toc, γ-Toc, δ-Toc, and T-Toc in maize [24,28,29], rapeseed (B. napus) [30][31][32], sunflower [33,34], and other plants [35].…”
Section: Introductionmentioning
confidence: 99%